Penelusuran Sumber Air dan Program Mitigasi terhadap Masalah Air di Dusun Guyangan Kidul - Abdullah Bagir; Akhmadi; Aldrian Bachtiar Tsani; Rafif Murti Rizky (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Water is an undeniable essence of life, serving as a fundamental need for all living organisms on our planet. Its importance extends beyond various ecosystems, playing a vital role in sustaining plants, animals, and humans. From providing nourishment to plants to supplying hydration to livestock, water plays a fundamental role in ensuring food security and supporting agricultural efforts. Moreover, water serves as the foundation for industrial processes, facilitating production across various sectors. Beyond its utilitarian value, water holds significant ecological importance, contributing to biodiversity conservation and preservation of natural habitats. Freshwater reservoirs serve as the primary source to meet various needs, including drinking and sanitation. However, it is crucial to acknowledge the challenges faced during drought seasons. Drought poses a serious threat not only disrupting water supplies for human and agricultural needs but also having broad impacts on ecosystems and environmental sustainability. These conditions can lead to significant economic losses, damaging agricultural yields, and even disrupting food supplies. Therefore, this paper aims to address the challenges posed by drought, particularly in the region of Padukuhan Guyangan Kidul, Kalurahan Mertelu, Kecamatan Gedangsari, Kabupaten Gunungkidul, by exploring the potential of groundwater sources and implementing strategies to mitigate the impacts of water scarcity. The methods employed include geoelectric surveys using Schlumberger configuration and 3D surface-frequency-depth analysis. The main results include the identification of potential groundwater sources and the implementation of filtration systems to improve water quality. In conclusion, this study highlights the importance of groundwater exploration and community engagement in addressing water scarcity issues, ultimately contributing to improved access to clean water and sustainable development in the region.